Números complexos e transformações geométricas - Paschoalino, Patrick Thiago (Universidade Federal de São Carlos, 2018)
The objective of this work was the development of a didactic sequence for the presentation of the set of complex numbers for the students of the third year of High School. The activities carried out prioritized the geometric approach, aiming at the application of operations in geometric transformations of figures (rotation, translation and homotetia), which represents one of the learning situations in the Student Book. These activities were carried out with the intention of minimizing the resistance and disinterest presented, in most cases, by students in relation to the content "Complex Numbers". Preliminary studies were carried out on the history and theory behind the didactic sequence.
Keywords: Números complexos; Transformações geométricas; Vetores; Representação no plano; Complex numbers; Geometric transformations; Vectors; Representation in the plane; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ALGEBRA